2019
DOI: 10.1096/fj.201802233r
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen‐induced liver injury is mediated by the ion channel TRPV4

Abstract: Overdosing of the analgesic acetaminophen (APAP) is one of the most common causes for acute liver failure in modern countries. Although the exact molecular mechanisms mediating hepatocellular necrosis are still elusive, it is preceded by oxidative stress triggered by excessive levels of the metabolite N‐acetyl‐para‐benzoquinone imine (NAPQI). Here, we describe the role of the redox‐sensitive transient receptor potential (TRP) ion channel TRP vanilloid 4 (TRPV4) for APAP‐induced hepatoxicity. Both pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…Despite its clear promise, some potential restrictions and caveats should not go unmentioned. First, systemic inhibition of TRPV4 could prove problematic because of potential effects on hepatic function, a concern that is particularly relevant in the critically ill (38), yet a hepatoprotective role of TRPV4 inhibition has also been postulated in acetaminophen toxicity (12). Notably, phase I clinical trials using a selective TRPV4 inhibitor did not detect increased liver enzymes in healthy volunteers or patients with congestive heart failure (17).…”
Section: Commentary and Caveatsmentioning
confidence: 99%
“…Despite its clear promise, some potential restrictions and caveats should not go unmentioned. First, systemic inhibition of TRPV4 could prove problematic because of potential effects on hepatic function, a concern that is particularly relevant in the critically ill (38), yet a hepatoprotective role of TRPV4 inhibition has also been postulated in acetaminophen toxicity (12). Notably, phase I clinical trials using a selective TRPV4 inhibitor did not detect increased liver enzymes in healthy volunteers or patients with congestive heart failure (17).…”
Section: Commentary and Caveatsmentioning
confidence: 99%
“…Another study by Echtermeyer and colleagues suggests that TRPV4 may also contribute to acetaminophen-initiated hepatocyte toxicity [ 69 ]. Liver damage, assessed by measurement of blood liver marker enzymes and liver histology, was substantially reduced in TRPV4 knockout mice compared to that in wild-type mice, and in wild-type mice treated with the TRPV4 inhibitor HCO67047.…”
Section: Trpm2 Channels Mediate Liver Injury Induced By Acetaminophen (Paracetamol) Toxicitymentioning
confidence: 99%
“…Patch clamp recording with HEK293T cells heterologously expressing TRPV4 showed that NAPQI activates a current with the characteristics of TRPV4. However, such a NAPQI-activated current was not observed in isolated mouse and human hepatocytes [ 69 ]. Further experiments are required to confirm that TRPV4 proteins are present in the hepatocyte plasma membrane and do, indeed, form functional TRPV4 channels in freshly isolated hepatocytes.…”
Section: Trpm2 Channels Mediate Liver Injury Induced By Acetaminophen (Paracetamol) Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…While no studies have directly evaluated liver fibrosis in TRPV4 KO mice, some data suggest that the absence of TRPV4 may be protective. TRPV4 KO mice exhibited reduced hepatotoxicity caused by high levels of acetaminophen, which can progress to liver fibrosis if lethality from acute liver failure does not occur first [140,141]. TRPV4 inhibition also reduced the activation of hepatic stellate cells, the matrix remodeling cells of the liver [142].…”
Section: Pathophysiological Functions Of Trpv4mentioning
confidence: 99%